A Power-Efficient Soft-Output Detector for Spatial-Multiplexing MIMO Communications. (1st March 2012) - Wang, Hsiao-Chi; Liu, Tung-Lin; Wu, Yuan-Wei; Ma, Hsi-Pin
Abstract : VLSI implementation of a configurable power-efficient MIMO detector is proposed to support 4 × 4 spatial multiplexing and modulation from QPSK to 64-QAM. A novel tree search algorithm is proposed to enable the detector to provide soft outputs and to be implemented in parallel and pipelined hardware architecture. The frame error rate (FER) of the detector approaches the quasi-optimal sphere decoder, with 0.5-dB degradation. Moreover, the proposed detector can operate at the optimal voltage under different configurations and detect/recover timing error at run time by a novel adaptive voltage scaling technique with double sampling circuitry. The proposed detector, using TSMC 0.18 μm single-poly six-metal CMOS process with a core area of 1 .17 × 1 .17  mm 2, provides fixed throughput of 45 Mbps in 64-QAM configuration, 120 Mbps in 16-QAM configuration, and 60 Mbps in QPSK configuration. The normalized power efficiency of the design for 64-QAM and 16-QAM configurations is 1.56 Mbps/mW and 2.53 Mbps/mW, respectively. Compared with the conservative margin-based design, the proposed design achieves a 48.8% power saving.